Source and Ecological Risk Characteristics of PAHs in Sediments from Qinhuai River and Xuanwu Lake, Nanjing, China - Zhenhua Zhao; Zhirui Qin; JingJing Cao; Liling Xia (Journal of Chemistry)
In order to investigate the residual characteristics, sources, and ecological risk of PAHs in sediment from urban rivers, the sediments of 15 typical sites from Qinhuai River and Xuanwu Lake, which are typical urban rivers and lake, were collected from October 2015 to July 2016; the sources of PAHs in sediment were also identified by several methods. Results showed that ∑PAHs concentration in sediment ranged from 796.2 ng/g to 10,470 ng/g with an average of 2,713.8 ng/g. High molecular weight PAHs with 4-5 rings were most prominent in the sediment during all four seasons. Source characterization studies based on the analysis of diagnostic ratio (triangular plot method), cluster analysis, and positive factor matrix analysis suggested that the PAHs of Qinhuai River Basin were mainly from pyrogenic origin (biomass and coal combustion and vehicular emission), and the petroleum source also cannot be ignored (specially in summer). Most individual PAHs occasionally affect the aquatic organisms. The highest benzo[a]pyrene-equivalent doses (BaPeq dose) appear at the sites of sewage discharge and heavy traffic. So, the PAHs pollution sources of urban water body have obvious seasonal-dependent and human activities-dependent characteristics.